Two Cases of Mastectomy after Paclitaxel + Bevacizumab Therapy for Locally Advanced Breast Cancer - Chika Shinoda; Ryutaro Mori; Yasuko Nagao (Case Reports in Oncology, 2014)
Introduction: Locally advanced breast cancer (LABC) deteriorates the quality of life (QOL) of the affected patients. Combination chemotherapy or extended chemotherapy is considered to help to shrink local lesions. Case 1: A 71-year-old female with a history of tympanitis and cystitis with methicillin-resistant Staphylococcus aureus (MRSA) visited our hospital. There was a tumor of 7 cm in diameter in her right breast with skin ulceration. Paclitaxel + bevacizumab therapy was started, and after five cycles of therapy, a mastectomy with axillary dissection was performed. Chemotherapy with anthracycline was avoided for fear of activating the MRSA. After the operation, the patient's wound opened. However, it naturally epithelialized. Case 2: A 41-year-old female visited our hospital due to a tumor of 8 cm in diameter in her right breast with skin ulceration. Four cycles of paclitaxel + bevacizumab therapy were started, and her tumor almost disappeared during the first cycle. Then, doxorubicin + cyclophosphamide therapy was performed for four cycles, and a mastectomy with axillary dissection was performed. Her postoperative course was good. Discussion: Chemotherapy with bevacizumab or extended chemotherapy is generally not considered to contribute to a survival improvement. However, such therapy contributes in increasing the response to chemotherapy, and should be considered for patients with LABC to shrink the local lesions and improve the QOL.